2004
DOI: 10.1021/bm049930r
|View full text |Cite
|
Sign up to set email alerts
|

AFM Study of the Elastin-like Biopolymer Poly(ValGlyGlyValGly)

Abstract: In this paper, we report an AFM study on the supramolecular structures adopted by the synthetic polypentapeptide poly(ValGlyGlyValGly), whose monomeric sequence is an abundant, simple building block of elastin. The polypeptide was analyzed by deposition from both methanolic and aqueous suspensions, showing different behaviors. In methanol, the polypeptide is able to evolve, in a time-dependent way, from layers to ribbons to beaded filaments. When the equilibrium is reached, the formation of well-defined dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 28 publications
6
93
0
Order By: Relevance
“…The length of the fibrils varied from hundreds of nanometers to several microns. Tamburro and colleagues (29) recently reported that the filament length of the analogue poly(ValGlyGlyValGly) peptide can reach 70 m, suggesting a possible mechanism of longitudinal alignment of the peptides besides a lateral one. Repeated AFM imaging performed over the same sample at different times (up to several months after sample preparation) revealed no significant morphological changes, indicating a remarkable stability of the fibrils at ambient conditions, which is in qualitative agreement with our previous data on solid-state protein films (30,31).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The length of the fibrils varied from hundreds of nanometers to several microns. Tamburro and colleagues (29) recently reported that the filament length of the analogue poly(ValGlyGlyValGly) peptide can reach 70 m, suggesting a possible mechanism of longitudinal alignment of the peptides besides a lateral one. Repeated AFM imaging performed over the same sample at different times (up to several months after sample preparation) revealed no significant morphological changes, indicating a remarkable stability of the fibrils at ambient conditions, which is in qualitative agreement with our previous data on solid-state protein films (30,31).…”
Section: Resultsmentioning
confidence: 99%
“…The polypentapeptides poly( ValGly GlyLeuGly) and poly(ValGlyGlyValGly) were chemically synthesized according to the procedures previously developed by Tamburro and colleagues (29,34).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite interestingly, the elastin-like biopolymer poly(VGGVG), which comprises the sequences LGGLG and VGGLG similar to those contained in EX30 peptide, has been shown to self-assemble in an amyloidlike pattern when deposited from aqueous suspensions (59). The fibrils did not solubilize after dilution, indicating the irreversibility of the process, also in this case.…”
Section: Discussionmentioning
confidence: 80%
“…[1][2][3][4] These interactions must be controlled to derive information on the aggregation phenomena occurring in important pathologies as amyloidosis, and indeed used, to ensure successful manufacturing of engineered bio-structures. [5][6][7] Such considerations have been of strength in our work on the formation of strong and stiff amyloid-like and non-amyloid fibers or agglomerates from elastin-like polypeptides (ELPs), poly (ValGlyGlyValGly), [8][9][10] and poly(ValGlyGlyLeuGly). [11][12][13] Using AFM to compare the macromolecular structures of these ELPs from aqueous and non-aqueous suspension we have found that the ratio of amyloid-like fibers depends on the water activity in the medium.…”
Section: Introductionmentioning
confidence: 99%